Reduction of molybdenum oxide from steelmaking slags by pure liquid iron - Gao Y.M.; Jiang Y.; Huang S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effects of reaction temperature, slag basicity and FeO concentration on the reduction of molybdenum oxide from steelmaking slags by pure liquid iron were investigated experimently. The reduction kinetics of molybdenum oxide by liquid iron was analysed. The reaction models were developed based on the condition that diffusion of [Mo] in liquid iron and CaMoO4 in slag is the control steps, respectively. These reaction models were tested using data from a series of experiments. The results indicate that under the present experimental conditions, the temperature and the FeO content, other than slag basicity, have some effects on the reduction of molybdenum oxide from steelmaking slags by pure liquid iron. Both the molybdenum oxide reduction rate and final reduction ratio increase with an increase of temperature and a decrease of FeO content. The diffusion of CaMoO4 in slag which dominated overall reduction process is the only one ratecontrolling step with its apparent activation energy 294 kJ/mol. The reduction of molybdenum oxide used directly as alloy additive can be further enhanced by strong stirring in the converter practice.